1983
DOI: 10.1111/j.1432-1033.1983.tb07407.x
|View full text |Cite
|
Sign up to set email alerts
|

Reguladtion of Citrate Efflux from Mitochondria Oleaginou and Non‐Oleaginous Yeasts by Adenine Nucleotides

Abstract: The regulation of mitochondrial citrate metabolism has been investigated in oleaginous and non-oleaginous yeasts to ascertain its importance in controlling the rate of citrate efflux from mitochondria. The following observations were made :1. Citrate efflux from mitochondria of the oleaginous yeast Candida curuata D, in the presence of L-malate and pyruvate, was stimulated by adding ATP and reduced by AMP. In the non-oleaginous yeast, Candida utilis 359, there was very little stimulation of citrate efflux by A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
2
2

Year Published

1983
1983
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 47 publications
0
33
2
2
Order By: Relevance
“…In contrast to results reported by Evans et al [9] aad Wills and Melham [71 the e~yme pyruvate carboxylase was found to be localized i~ the cytosol in bodl S. cerevisiae and C. utilis. It c,~u~d be argued that this would result from leakage of the enzyme from the mitochondrial matrix.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to results reported by Evans et al [9] aad Wills and Melham [71 the e~yme pyruvate carboxylase was found to be localized i~ the cytosol in bodl S. cerevisiae and C. utilis. It c,~u~d be argued that this would result from leakage of the enzyme from the mitochondrial matrix.…”
Section: Discussioncontrasting
confidence: 99%
“…However, in contrast to the report by Evans et al [9], also in C. utilis the enzyme was exclusively recovered in the soluble fraction (Table I). The activity of the enzyme was approximately the same in both organisms.…”
Section: Subcellular Localization and Activities Of Pyruvate-metaboiicontrasting
confidence: 99%
See 1 more Smart Citation
“…Efflux of citrate could be controlled by (a) limiting the amount of intramitochondrial citrate made available for binding to the citrate translocase in the inner mitochondrial membrane, (b) by the availability of cytosolic L-malate as counter-anion for the operation of the citrate-malate exchange and (c) by directly affecting the efficiency of the citrate carrier from promoting exchange. The importance of points (a) and (b) with regard to oleaginicity in yeasts has been discussed previously [5,6]. The direct regulation of the mitochondrial carrier by long-chain fatty-acyl-CoA esters forms the subject of this report.…”
mentioning
confidence: 99%
“…The following yeasts were used in this study: Methods used for growth of yeasts, lipid extraction and preparation of mitochondria were as reported earlier [5]. Citrate was assayed enzymatically [36] in supernatants and mitochondrial extracts.…”
Section: Yeastsmentioning
confidence: 99%